Implications of the 2000 watt society for urban planning and economics. - Melanie Lienhard (European Regional Science Association (ERSA), 2014)
Based on the increasing popularity and dispersal of the concept of the 2000 watt society the paper analyses what defines the concept and what kind of implications it has including the challenges in regards to urban planning and economics. The literature analysis has shown that a sufficient amount of research in regards to the implementation of the concept exists solely in the area of building technology. For further analysis a selection of criteria has been met which include: ? Mobility ? Living and Working ? Architecture and building typology ? Consumption ? Usage and user behaviour
Keywords: 330; Urbanisation; Environment; Energy; Regional Economics; R11 Regional Economic Activity: Growth; Development; and Changes